A Rapid Review of the Impact of Systems-Level Policies and Interventions on Population-Level Outcomes Related to the Opioid Epidemic, United States and Canada, 2014-2018. (July 2020) - Ansari, Bahareh; Tote, Katherine M.; Rosenberg, Eli S.; Martin, Erika G.
Objectives: In the United States, rising rates of overdose deaths and recent outbreaks of hepatitis C virus and HIV infection are associated with injection drug use. We updated a 2014 review of systems-level opioid policy interventions by focusing on evidence published during 2014-2018 and new and expanded opioid policies. Methods: We searched the MEDLINE database, consistent with the 2014 review. We included articles that provided original empirical evidence on the effects of systems-level interventions on opioid use, overdose, or death; were from the United States or Canada; had a clear comparison group; and were published from January 1, 2014, through July 19, 2018. Two raters screened articles and extracted full-text data for qualitative synthesis of consistent or contradictory findings across studies. Given the rapidly evolving field, the review was supplemented with a search of additional articles through November 17, 2019, to assess consistency of more recent findings. Results: The keyword search yielded 535 studies, 66 of which met inclusion criteria. The most studied interventions were prescription drug monitoring programs (PDMPs) (59.1%), and the least studied interventions were clinical guideline changes (7.6%). The most common outcome was opioid use (77.3%). Few articles evaluated combination interventions (18.2%). Study findings included the following: PDMP effectiveness depends on policy design, with robust PDMPs needed for impact; health insurer and pharmacy benefit management strategies, pill-mill laws, pain clinic regulations, and patient/health care provider educational interventions reduced inappropriate prescribing; and marijuana laws led to a decrease in adverse opioid-related outcomes. Naloxone distribution programs were understudied, and evidence of their effectiveness was mixed. In the evidence published after our search's 4-year window, findings on opioid guidelines and education were consistent and findings for other policies differed. Conclusions: Although robust PDMPs and marijuana laws are promising, they do not target all outcomes, and multipronged interventions are needed. Future research should address marijuana laws, harm-reduction interventions, health insurer policies, patient/health care provider education, and the effects of simultaneous interventions on opioid-related outcomes.